Relationship between hair nicotine levels with blood pressure, body composition, lipid profile and leptin among healthy male smokers in Kelantan. Issue 1 (February 2016) - Sanip, Zulkefli B.; Suhaimi, Muhammad Z.B.; Man, Che N.; Rasool, Aida H.B.G.; Yusoff, Harmy B.M.
الملخص: أهداف البحث: هناك تقارير تؤيد أن تدخين السجائر يسبب ارتفاعا حادا في ضغط الدم. لذا٬ من المهم تقييم العلاقة بين التدخين المزمن٬ وضغط الدم٬ ومكونات الجسم٬ وملف الأيض الشخصي لإدراك التأثيرات طويلة الأمد للتدخين على وزن الجسم وصحته. بحثت هذه الدراسة العلاقة بين مستويات النيكوتين في الشعر٬ وضغط الدم٬ ومكونات الجسم٬ ومستوى الدهون٬ والليبتين بين المدخنين الذكور الأصحاء. طرق البحث: في هذه الدراسة المقطعية٬ تطوع للدراسة ١٠٧ من المدخنين الذكور تتراوح أعمارهم بين ٢٠-٥٠ عاما. تم قياس مستويات النيكوتين في الشعر باستخدام مقياس الطيف اللوني الغازي للكتلة. كما تم قياس ضغط الدم٬ ومكونات الجسم (الوزن٬ والطول٬ ومؤشر كتلة الجسم٬ ونسبة الدهون في الجسم٬ والدهون بالأحشاء٬ ومحيط الخصر والورك٬ بالإضافة إلى معدل الأيض) ومستوى الدهون٬ وتركيز الليبتين وفقا لذلك. النتائج: كان متوسط العمر ومؤشر كتلة الجسم بين الأشخاص ٣٧ عاما و ٥٩¸٢٤ كجم⁄ م٢٬ على التوالي. وسجلت متوسط فترة التدخين ١٦.٩١ عاما. كما سجلت مستويات النيكوتين بالشعر بإيجابية مع الكوليسترول الكلي٬ ومستويات الدهون الثلاثية. لكن لم يكن هناك ارتباط كبير بين ضغط الدم٬ ومكونات الجسم٬ وتركيز الليبتين. الاستنتاجات: العلاقة الإيجابية بين مستويات النيكوتين بالشعر٬ والكوليسترول الكلي٬ والدهون الثلاثية حددت الآثار الضارة للتدخين المزمن حتى بين المدخنين الذكور الأصحاء. Abstract: Objectives: Cigarette smoking has been reported to cause acute blood pressure elevation. Therefore, it is important to assess the relationships between chronic smoking and blood pressure, body composition, and the metabolic profile to gain an understanding of the long-term effects of smoking on an individual's body weight and health. This study examined the relationships between the hair nicotine level, blood pressure, body composition, lipid profile, and leptin in healthy male smokers. Methods: For this cross-sectional study, 107 male smokers aged between 20 and 50 years old were recruited as volunteers. The nicotine levels in the volunteers' hair were measured using gas chromatography-mass spectrometry. Moreover, the subjects' blood pressure, body composition (weight, height, body mass index, body fat percentage, visceral fat, waist and hip circumferences, and basal metabolic rate), lipid profile, and leptin concentration were also measured. Results: The means for age and BMI among the subjects were 37.00 (9.42) years and 24.59 (4.33) kg/m 2, respectively. The average length of time as a smoker was 16.91 years. The hair nicotine level was found to be positively correlated with the total cholesterol (r = 0.314, r 2 = 0.099, p = 0.028) and triglyceride (r = 0.351, r 2 = 0.0.123, p = 0.013) levels. However, no significant correlations were found between the hair nicotine level and blood pressure, body composition, or leptin concentration. Conclusion: The positive correlations between the hair nicotine level and total cholesterol and triglyceride levels highlighted the harmful effects of chronic smoking, even among healthy male subjects.